2019
DOI: 10.3390/min9090512
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Infrared Spectra for Hydrous Forsterite up to 1243 K: Hydration Effect on Thermodynamic Properties

Abstract: Hydrogen substitution has significant effect on the physical properties of olivine, the most abundant mineral in the upper mantle. We collected high-temperature polarized Fourier Transform infrared (FTIR) spectra on hydrous forsterite (Mg-pure olivine) crystals, which were synthesized at 12 GPa, 1473–1673 K. The modes at 3612, 3578, 3566, 3551 cm−1 show comparable negative temperature dependence, and the magnitude of (∂vi/∂T)P decreases dramatically with frequency increasing. Whereas, the peak at 3477 cm−1, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(191 reference statements)
1
5
0
Order By: Relevance
“…conditions (e.g. Gillet et al 1991;Liu et al 2019b), and this study reveals that Fe incorporation further increases the magnitudes of these contribution. In addition, previous high-temperature studies have indicated that Fe decreases the thermal expansion coefficient in olivine solid solutions (Smyth and Hazen 1973;Smyth 1975; This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Implicationsupporting
confidence: 57%
See 2 more Smart Citations
“…conditions (e.g. Gillet et al 1991;Liu et al 2019b), and this study reveals that Fe incorporation further increases the magnitudes of these contribution. In addition, previous high-temperature studies have indicated that Fe decreases the thermal expansion coefficient in olivine solid solutions (Smyth and Hazen 1973;Smyth 1975; This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Implicationsupporting
confidence: 57%
“…Kohlstedt et al 1996;Smyth et al 2006). The calculation revealed that hydration would further increase the magnitude of the anharmonic contribution to more than 9 % for the model of the heat capacities (Liu et al 2019b).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The temperature dependences of the OH-stretching modes, (∂ν i /∂T) P , for humite-group minerals are compared with other dense hydrous Mg-silicate minerals in the peridotite system (MgO-SiO 2 -Mg(OH) 2 ) ( Fig. 7), such as serpentine, brucite, talc, phases A, B, E and super hydrous phase B (Liu et al 1997a(Liu et al , 1997b(Liu et al , 1998(Liu et al , 1999(Liu et al and 2002Lin et al 1999 and2000;Zhang et al 2006;Trittschack et al 2012;Liu et al 2019a and2019b;Zhu et al 2019; this study). The OH bands above 3450 cm -1 typically show a negative temperature dependence, whereas those below 3450 cm -1 typically exhibit a positive temperature dependence.…”
Section: Oh-stretching Bands and Temperature Dependencementioning
confidence: 99%
“…In contrast, a minor fraction of the Mg-Rw thin section annealed at 600 • C for the cumulated annealing time of 30 min may have transited to forsterite, as indicated by the tiny new Raman peak at ~857 cm −1 . Nevertheless, the infrared spectrum 1589-06-03 (Figure 10f), probing both the surface material and the interior material of the thin section, show water peaks completely different to those of forsterite [84][85][86][87], implying a totally negligible amount of phase transition. For the purpose of comparison, the IR spectrum collected for each thin section before the annealing experiments is also shown at the bottom of each graph.…”
Section: Ir Features Of Water In Mg-rw Annealed At Different T: a Sum...mentioning
confidence: 99%